Effect of Aloe vera and vitamin E supplementation on the immune response of broilers - Babak Darabighane (Universidad de Antioquia, 2017)
Background: herbs are among the feed supplements under investigation that could replace antibiotics to improve humoral and cellular immune response in birds. Objective: this study evaluated the potential of Aloe vera (Aloe barbadensis Miller) and vitamin E as immunostimulants on humoral and cellular immune responses in broilers. Methods: broilers were randomly assigned to three dietary treatments: a negative control (basal diet + with no additive), basal diet + 1% Aloe vera gel in drinking water, and basal diet + 100 mg/Kg vitamin E in the feed. Antibody titers against sheep red blood cells and Newcastle disease virus were used to examine the humoral immune response, whereas cellular immune response was evaluated using the phytohemagglutinin-P tests. Results: the highest level of antibody titer against sheep red blood cells on examination days 28 and 38, and the highest response to injection of phytohemagglutinin-P on day 38 was observed in the Aloe vera gel group (p<0.05). However, the response of broilers fed Aloe vera gel was not different from those receiving vitamin E (p>0.05). In addition, the greatest antibody level against Newcastle disease virus was obtained on days 25 and 35 in the vitamin E group, with no significant difference from the Aloe vera gel group (p>0.05). Conclusion: in general, our findings demonstrated that both Aloe vera gel and vitamin E can enhance humoral and cellular immune responses of broilers, while Aloe vera gel can be used as an immunostimulant in chickens.